Whole-exome sequencing identifies recessive WDR62 mutations in severe brain malformations - Bilgüvar, Kaya; Öztürk, Ali Kemal; Louvi, Angeliki; Kwan, Kenneth Y.; Choi, Murim; Tatlı, Burak; Yalnızoğlu, Dilek; Tüysüz, Beyhan; Çağlayan, Ahmet Okay; Gökben, Sarenur; Kaymakçalan, Hande; Barak, Tanyeri; et al. (Nature (London), 2010)
Gene linked to brain malformation The identification of genetic loci linked to abnormal cortical development is complicated by genetic heterogeneity, small family sizes and diagnostic classifications that do not reflect molecular pathogenesis. These obstacles have been overcome in a study using whole-exome sequencing. Recessive mutations in the WD repeat domain 62 ( WDR62 ) gene are shown to cause a wide spectrum of seemingly disparate brain abnormalities, including microcephaly, pachygyria and, in one instance, cerebellar hypoplasia. Unlike other known microcephaly genes, WDR62 does not associate with centrosomes; it is predominantly nuclear in localization and is expressed transiently in the neocortex during embryonic neurogenesis. Mapping disease loci that underlie putative Mendelian forms of malformations of cortical development is complicated by genetic heterogeneity, small family sizes and diagnostic classifications that may not reflect molecular pathogenesis. These authors use whole-exome sequencing to identify recessive mutations in WDR62 as the cause of a wide spectrum of severe cerebral cortical malformations. WDR62 's nuclear localization to germinal neuroepithelia indicates that cortical malformations can be caused by events during progenitor proliferation and neurogenesis. The development of the human cerebral cortex is an orchestrated process involving the generation of neural progenitors in the periventricular germinal zones, cell proliferation characterized by symmetric and asymmetric mitoses, followed by migration of post-mitotic neurons to their final destinations in six highly ordered, functionally specialized layers 1 , 2 . An understanding of the molecular mechanisms guiding these intricate processes is in its infancy, substantially driven by the discovery of rare mutations that cause malformations of cortical development 3 , 4 , 5 , 6 . Mapping of disease loci in putative Mendelian forms of malformations of cortical development has been hindered by marked locus heterogeneity, small kindred sizes and diagnostic classifications that may not reflect molecular pathogenesis. Here we demonstrate the use of whole-exome sequencing to overcome these obstacles by identifying recessive mutations in WD repeat domain 62 ( WDR62 ) as the cause of a wide spectrum of severe cerebral cortical malformations including microcephaly, pachygyria with cortical thickening as well as hypoplasia of the corpus callosum. Some patients with mutations in WDR62 had evidence of additional abnormalities including lissencephaly, schizencephaly, polymicrogyria and, in one instance, cerebellar hypoplasia, all traits traditionally regarded as distinct entities. In mice and humans, WDR62 transcripts and protein are enriched in neural progenitors within the ventricular and subventricular zones. Expression of WDR62 in the neocortex is transient, spanning the period of embryonic neurogenesis. Unlike other known microcephaly genes, WDR62 does not apparently associate with centrosomes and is predominantly nuclear in localization. These findings unify previously disparate aspects of cerebral cortical development and highlight the use of whole-exome sequencing to identify disease loci in settings in which traditional methods have proved challenging.